Analisis Kebijakan Dinas Kependudukan dan Pencatatan Sipil dalam Layanan Administrasi Pendataan Penerima Bansos COVID-19 di Kota Malang - Yanuarita, Heylen Amildha; Susanto, Djoko (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The increase in population in Malang City can encourage the implementation of good population data recording, this is because population data is very important in planning and development in the evaluation stage. The purpose of this research is to analyze the policies of the population service and civil registration in the administrative services for data collection on Covid-19 social assistance recipients in Malang City. This research is a descriptive research with a qualitative approach. The population administration policy in this study is focused on administrative services for the data collection of Covid-19 Social Assistance Receipts in Malang City. The results of this study indicate that there is a policy of centralizing the management of resident identification cards, the first step to progress in the city government of Malang, especially in the field of administrative services for data collection on Covid-19 Social Assistance Recipients in Malang City so that they try to make other policies that have concrete data.